Democratization by elections : a new mode of transition - Lindberg, Staffan I. 1969- (Johns Hopkins Univ. Press, 2009)
The power of elections in Africa revisited / Staffan I. Lindberg -- The relative powerlessness of elections in Latin America / Jennifer L. McCoy and Jonathan Hartlyn -- Elections as levers of democratization: a global inquiry / Jan Teorell and Axel Hadenius -- Post-Cold War political regimes: when do elections matter? / Philip G. Roessler and Marc M. Howard -- Harbinger of democracy: competitive elections before the end of authoritarianism / Jason Brownlee -- All elections are not the same: why power-sharing elections strengthen democratization / Pippa Norris -- Sources of competition under electoral authoritarianism / Andreas Schedler -- Opposition parties and incumbent presidents: the new dynamics of electoral competition in Africa / Lise Rakner and Nicolas van de Walle -- Legislative elections in hegemonic authoritarian regimes: competitive clientelism and resistance to democratization / Ellen Lust-Okar -- Opposition versus dictators: explaining divergent electoral outcomes in post-Communist Europe and Eurasia / Valerie J. Bunce and Sharon L. Wolchik -- Judicial complexity empowering opposition? Critical elections in Armenia and Georgia / Bryon Moraski -- The contingent power of authoritarian elections / Andreas Schedler -- A theory of elections as a mode of transition / Staffan I. Lindberg